2018
DOI: 10.1186/s12877-018-0836-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of 27 plasma immune markers: a cross-sectional comparison of 64 old psychiatric inpatients having unipolar major depression and 18 non-depressed old persons

Abstract: BackgroundThe prevalence of major depression (MD) according to population studies is the same for old (65 years and older) and younger adults. In contrast, an elevated proportion of old MD patients are hospitalized compared to younger adults with MD, indicating a need to expand the characteristics of old inpatients with MD. To illustrate this point, the association between inflammation and MD in old psychiatric inpatients is sparsely investigated even though an association between inflammation and treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
1
17
1
2
Order By: Relevance
“…Elevated levels of IL‐6 and TNF‐α are also commonly found in the serum of patients with major depressive disorder (MDD) . Systemically increased C‐reactive protein (CRP) and IL‐1β have been reported in depressed patients, while IL‐8 and IL‐17 have shown high specificity and high sensitivity, respectively, for depression in elderly subjects .…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of IL‐6 and TNF‐α are also commonly found in the serum of patients with major depressive disorder (MDD) . Systemically increased C‐reactive protein (CRP) and IL‐1β have been reported in depressed patients, while IL‐8 and IL‐17 have shown high specificity and high sensitivity, respectively, for depression in elderly subjects .…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
“…Elevated levels of IL‐6 and TNF‐α are also commonly found in the serum of patients with major depressive disorder (MDD) . Systemically increased C‐reactive protein (CRP) and IL‐1β have been reported in depressed patients, while IL‐8 and IL‐17 have shown high specificity and high sensitivity, respectively, for depression in elderly subjects . However, a meta‐analysis published in 2015 that included 58 studies involving MDD patients and a meta‐analysis published in 2016 that included 30 studies involving MDD patients showed no significant changes in systemic IL‐1β .…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
“…Depression and schizophrenia seem to dominate this research, both disorders repeatedly demonstrating elevated levels of pro-inflammatory cytokines such as IL-1β, IL-2, IL-6, and TNF [ 1 3 ]. Though some of these studies include elderly patients [ 4 6 ], most studies have been conducted on younger adults. Thus, there is a paucity of studies on elderly psychiatric patients and particularly elderly psychiatric in-patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although rectal temperatures predicted and thus could serve as surrogate markers for brain temperatures in SIV-infected monkeys under the conditions we studied, brain temperatures do not always correlate with peripheral temperature measures. 32,33 Thus, brain temperature can be a useful independent measure and could be informative in other brain disorders, including in major depression, which is associated with inflammation, [50][51][52] as well as in addiction disorders, 32,53,54 psychotic disorders, [55][56][57] seizure disorders, 58 and stroke. 59,60…”
Section: Discussionmentioning
confidence: 99%